The benefits of an having an independent telecommunications regulatory authority: a SADC perspective - Chakauya, Christine Fadzai (Centre for Law and Society, 2026)
The research paper has a fourfold goal in highlighting the role of an independent regulat9ry authority in the telecommunications sector. The backdrop of the analysis will be on the ability of the telecommunications regulator to maintain independence whilst at the same time diligently• carry out designated duties. Chapter one delves into the history of chosen case studies on Zimbabwe and South Africa focusing on their paths to privatization and individual impact that the independent regulator has had on the industry. The argument being, although they have similar origins as regards their background to telecommunications, the diverse environments in which the independent regulators operate are different. Therefore the intended results will inevitably vary individually. Assessment will be on the impact on telephony, particularly on cellular operators and not on broadcasting. Chapter 2 seeks to explore the importance of independence in the regulators office. An in-depth consideration the reasons affecting the ability to be independent will be highlighted. The chapter focuses on the importance of the role of the regulator taking into consideration the guidelines as recommended by the World Trade Organization. Bearing in mind the case studies have similar origins in telecommunicatiQns, the diverse environments in which the independent regulators operate are different. Therefore the intended results will inevitably vary individually. Chapter 3 analyses functions of the regulator and the frameworks adopted to achieve desired goals. Suggestions on prospective reforms of the institution of the independent regulators will be analysed, as a comparison of the chosen case studies. South Africa and Kenya will be used as comparisons, looking to how they have handled problematic issues such as interconnection which some developing nations are still coming to grips with. The diverse nature of the respective institutions would be effective in showing that where impartiality exists it contributes to the independence of the regulators. An in-depth consideration of commitments made to the World Trade Organisation will be tallied against individual performance in promoting competition on the market. The concluding chapter will look at possible solutions when it comes to tackling potential problematic issues, such as interconnection. An analysis of the telecommunications industries of the United States of America, Canada and Australia will be taken.